Deconstruction of Visual Aesthetics and Ideological Myths of Digital Preaching on the Instagram Account @hanan_attaki - Iin Indrawati Budi Utami; Dewi Anggrayni (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study examines the evolution of religious messaging in the digital realm, driven by the need to understand the impact of visualization on young audiences' perceptions of faith amidst increasingly crowded social networks. The research aims to dissect the formation of meaning in online da'wah activities by examining the complex blend of visual elements and storylines on the Instagram account @hanan_attaki from 2021 to 2025. The primary focus is on examining how religious intermediaries transform conventional teachings into emotionally charged personal experiences, presented specifically for Gen Z. Using a descriptive qualitative approach through virtual ethnography and Roland Barthes's semiotic analysis, this study meticulously breaks down digital codes down to the levels of denotation, connotation, and myth. This methodology allows for an in-depth exploration of how digital content creators manipulate symbols to align with contemporary sensibilities. The study reveals that the use of cinematic backdrops, soothing color gradations, and intimate appearances successfully constructs a significant new ideological myth: